EFFICIENCY OF THE METHODOLOGY FOR DEVELOPING THE MOTOR QUALITIES OF SCHOOLCHILDREN IN SPORTS LESSONS - Kim V.G. (Journals Park Publishing, 2023)
The article presents the results of a pedagogical experiment on the introduction of the author's methodology of accentuated physical education classes with a training focus on the basis of pedagogical testing, annual monitoring of the level of physical status of children aged 6-7 years with their comparative analysis and correlation between analyzed indicators.
Keywords: Accented classes, monitoring, motor fitness, standard, correlation, test, functional training.